PURPL and NEAT1 Long Non-Coding RNAs Are Modulated in Vascular Smooth Muscle Cell Replicative Senescence - Clara Rossi; Marco Venturin; Jakub Gubala; Angelisa Frasca; Alberto Corsini; Cristina Battaglia; Stefano Bellosta (Biomedicines, 2023)
Cellular senescence is characterized by proliferation and migration exhaustion, senescence-associated secretory phenotype (SASP), and oxidative stress. Senescent vascular smooth muscle cells (VSMCs) contribute to cardiovascular diseases and atherosclerotic plaque instability. Since there are no unanimously agreed senescence markers in human VSMCs, to improve our knowledge, we looked for new possible senescence markers. To this end, we first established and characterized a model of replicative senescence (RS) in human aortic VSMCs. Old cells displayed several established senescence-associated markers. They stained positive for the senescence-associated β-galactosidase, showed a deranged proliferation rate, a dramatically reduced expression of PCNA, an altered migratory activity, increased levels of TP53 and cell-cycle inhibitors p21/p16, and accumulated in the G1 phase. Old cells showed an altered cellular and nuclear morphology, downregulation of the expression of LMNB1 and HMGB1, and increased expression of SASP molecules (IL1β, IL6, IL8, and MMP3). In these senescent VSMCs, among a set of 12 manually selected long non-coding RNAs (lncRNAs), we detected significant upregulation of PURPL and NEAT1. We observed also, for the first time, increased levels of RRAD mRNA. The detection of modulated levels of RRAD, PURPL, and NEAT1 during VSMC senescence could be helpful for future studies on potential anti-aging factors.